Profile Protein "Brucella Abortus" Local Isolate with SDS Page Method - Desty Apritya; Didik Handijatno; Ratih Ratnasari (VITEK : Bidang Kedokteran Hewan, 2014)
The aim of this research was to find out the profile protein Brucella abortus local isolate. The samples bacteries were obtained from Balai Besar Veteriner Maros, South Sulawesi. Whole protein was obtained from Brucella abortus local isolate by ultrasonic homogenizer. The protein profile was analyzed by Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) with 4% stacking gel, 12% separating gel and standard of molecular weight was 10 – 200 kDa.The results of this research showed that the profile protein had seven fractions there were 112 kDa, 72 kDa, 54 kDa, 46 kDa, 41 kDa, 31 kDa and 20 kDa.